A Three-Echelon Healthcare Supply Chain Model for Blood Distribution During Crisis Times - Amir Khiabani; Alireza Rashidi Komijan; Amir Karbassi Yazdi; Yong Tan; Giuliani Coluccio Piñones; Alessio Ishizaka (Systems)
We aim to implement a three-tiered healthcare supply chain model within the context of a portable blood hub during times of crisis to provide healthcare to the most vulnerable populations. Due to a lack of blood, the number of deaths related to this issue has significantly increased in recent years. A critical challenge for healthcare decision-makers is the efficient distribution of blood among different centers. This research proposes a new method to address this issue, simplifying future solutions to similar problems. As a result of our findings, we introduce a model that considers three tiers in healthcare blood supply: point one (blood collection centers), point two (blood hubs), and final destinations (hospitals and clinics) during disasters. For this study, we focused on six collection sites, five blood centers, and thirty-one medical facilities providing eight different blood types. Our model demonstrates that blood can be transported from collection sites to medical centers at a lower cost during crises. This approach requires considering the full three tiers of the healthcare supply chain rather than focusing solely on the supply chain level at blood hubs. Unlike previous studies, which focused only on individual levels of supply chain management, this study examined the entire value chain, from blood collection to delivery to the end recipient.